The Effect of Related Party Transactions on Company Values with Good Corporate Governance as a Moderating Variable (An Empirical Study of State-Owned Enterprises 2021-2023) - Tri Candra Anggraini; Yuliusman Yuliusman; Yudi Yudi (International Journal of Economic Research and Financial Accounting, 2025)
This study aims to 1) Test the significant influence of Related Party Transactions on Company Value in State-Owned Enterprises listed on the Indonesia Stock Exchange for the 2021-2023 period. 2) Test whether the Good Corporate Governance variable can strengthen or weaken Related Party Transactions on Company Value in State-Owned Enterprises listed on the Indonesia Stock Exchange for the 2021-2023 period. This study uses a quantitative approach with the type of data used being secondary data. The sample used is a state-owned enterprise listed on the IDX and published complete financial reports for the 2021-2023 period. The results obtained are 1) This result can be interpreted that Related Party Transactions reflected by the indicator of the proportion of related party transactions to total assets can directly affect company value reflected by the Tobin's Q indicator. 2) The Good Corporate Governance variable can weaken Related Party Transactions on Company Value in State-Owned Enterprises listed on the Indonesia Stock Exchange for the 2021-2023 period.